1979
DOI: 10.1111/j.1365-2125.1979.tb05812.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beta‐adrenoceptor blockade on factors affecting exercise tolerance in normal man.

Abstract: 1 We have studied the effects of single oral doses of 80 mg propranolol and 100 mg metoprolol on the cardiovascular and respiratory responses to progressive exercise in nine healthy men in doubleblind, placebo-controlled experiment. As judged by their effects on exercise heart rate and cardiac output the doses of the two drugs used were equivalent.2 fp-adrenoceptor blockade reduced oxygen consumption by 3.5% over the whole work range with an increase in the respiratory exchange ratio of 0.056 units. Carbon dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
46
3
6

Year Published

1980
1980
1998
1998

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 20 publications
11
46
3
6
Order By: Relevance
“…Previous studies have reported conflicting results regarding the effect of P-adrenoceptor blockade on Vo, during submaximal exercise, as both a reduction [ 3,131 and no effect have been found [2, metabolic adaption may also explain our finding of reduced plasma lactate concentrations after chronic propranolol treatment. Such an adaption also appears to take place in the ischaemic myocardium where the administration of propranolol causes reduced myocardial oxygen requirement and a shift in substrate utilization with improvement of lactate metabolism from substantial production to extraction [45].…”
Section: Discussioncontrasting
confidence: 32%
“…Previous studies have reported conflicting results regarding the effect of P-adrenoceptor blockade on Vo, during submaximal exercise, as both a reduction [ 3,131 and no effect have been found [2, metabolic adaption may also explain our finding of reduced plasma lactate concentrations after chronic propranolol treatment. Such an adaption also appears to take place in the ischaemic myocardium where the administration of propranolol causes reduced myocardial oxygen requirement and a shift in substrate utilization with improvement of lactate metabolism from substantial production to extraction [45].…”
Section: Discussioncontrasting
confidence: 32%
“…The effects of the P-adrenoceptor antagonists on the heart rate response to progressive ergometer exercise are entirely consistent with previous studies (Anderson et al, 1979;Pearson et al, 1979;Wilcox et al, 1984 Lxolol. rate during the day or over 24 h (Carrageta et al, 1982;Floras et al, 1982;Rowlands et al, 1982).…”
Section: Pedometer Step-countssupporting
confidence: 80%
“…In fact, similar studies did not always show consistent results. For instance, all studies performed on healthy subjects who were able to reach high work rates (usually more than 200 W) showed a reduction of oxygen uptake and maximum work capacity after 3-adrenoceptor blockade (Pearson et al, 1979;Anderson et al, 1979;Twentyman et al, 1981;Tesch & Kaiser, 1983;Petersen et al, 1983), whereas no changes were found in studies carried out in subjects unable to reach such work levels, either healthy (Leitch et al, 1980) or suffering from mild hypertension (Fagard et al, 1980).…”
Section: Introductionmentioning
confidence: 99%